Negative thermal expansion, optical and electrical properties of HfMnMo2PO12−δ. Issue 10 (December 2015) - Zhang, Niu; Zhou, Wenjin; Chao, Mingju; Mao, Yanchao; Guo, Juan; Li, Yuxiang; Feng, Dongsheng; Liang, Erjun
Abstract: A new type of negative thermal expansion (NTE) material HfMnMo2 PO12− δ was synthesized using a solid state method, and its NTE, optical and electrical properties were systematically studied. HfMnMo2 PO12− δ exhibited NTE property from room temperature (RT) to 420 K with the coefficient of thermal expansion (CTE) −3.59×10 −6  K −1 . The coupling rotation of RUMs caused by transverse vibrations of bridge-O atoms and distortion of polyhedral due to Jahn–Teller effect and oxygen vacancies are attributed to the NTE behavior. The electrochemical impedance presents positive thermal coefficient (PTC) effect (RT – 420 K) at extremely low frequency, where the temperature scope coinciding to that of its NTE indicates an interesting internal relation. The electron scattering caused by vacancy defect contribute to the PTC effect. And the oxygen vacancy and Jahn–Teller effect were confirmed by the absorption and photoluminescence spectra.